Safety and efficacy of BioWorma® (Duddingtonia flagrans NCIMB 30336) as a feed additive for all grazing animals. (23rd July 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of BioWorma ® ( Duddingtonia flagrans NCIMB 30336) when used as a zootechnical feed additive for all grazing animals. Duddingtonia flagrans belongs to a group of nematophagous fungi that physically entrap nematodes through an adhesive hyphal net. The additive contains the fungus in the form of chlamydospores and is intended to control pathogenic nematodes on pasture, with subsequent benefits for grazing animals. No conclusions could be drawn on the safety for the target species due to lack of data. ■■■■■ As it is not possible to exclude the presence of secondary metabolites (other than flagranones) produced during fermentation and their potential carry‐over into animal products, safety for the consumer could not be established. The Panel concluded that the additive is not irritant to skin and eyes but is irritant to the respiratory tract and a respiratory sensitiser. No conclusion could be drawn on its skin sensitisation potential. Since D. flagrans is a naturally inhabiting soil organism of world‐wide distribution, the Panel considered that use of an additive based on this organism does not pose a risk for the environment under the intended conditions of use. The strain under application reduced the number of parasitic nematodes on pasture to the benefit of grazing animals when used at the recommended application rate of 3 × 10 4 chlamydospores/kg bodyweight and day.